Estudo do padrão de emissão de poluentes para o enquadramento de rios intermitentes: estudo de caso do Rio Salgado, Ce - Sabiá, Rodolfo José (2008)
This study was carried out on a 50 km length of the Salgado River, aiming to propose a methodology to determine an adequate pattern of pollutants emission, compatible with the natural recovery capacity of a river in a semi-arid region. The following steps were taken: (i) characterization of the study area based on the map of Salgado river and its tributaries; (ii) water quality diagnostic (Phase I, 1300 analysis): from March to September, 2005, in which eight river sections were selected for sampling, and 27 parameters were analysed in six monitoring campaigns; (iii) water quality diagnostic (Phase II, 1500 analysis): from February 2006 to January 2007, composed of twelve monitoring campaigns in 14 river sections with the parameters DO, BOD, faecal coliforms, total coliforms, pH, turbidity, electric conductivity, water and air temperature; (iv) social experiment, a participatory process involving CSBH-Salgado (Salgado Watershed Committee) and other social actors of the study watershed, promoting the discussion on water quality classification; (v) water quality modelling with the QUAL-2E model, calibrating two parameters: BOD and coliforms decay coefficients. Model validation was carried out using twelve campaigns from February 2006 to January 2007, distinguishing wet and dry periods. Scenarios simulation was performed for the BOD emission pattern with concentrations varying from 5 to 100 mg/L, and for the coliforms pattern with concentrations from 103 to 107 PN/100mL. This thesis concludes that the Salgado River, on the study reach, is polluted. It was identified that at least five parameters are in disagreement with the quality standards, inclusive for the Class IV: dissolved oxygen (DO), biochemical oxygen demand (BOD), faecal coliforms (FC), ammonia nitrogen and total phosphorus. The model was valid for the DO, BOD and FC simulations for the wet period, with Nash and Sutcliffe coefficient (NSE) from 0.61 to 0.96. For the dry period, the model was acceptable for DO and BOD (NSE) from 0.33 to 0.49) and valid for FC (NSE 0.83). The social actors identified the “emission patterns” as an essential instrument for the watershed environmental sustainability. The proposal of this research in admitting a “tolerance” to the water quality parameters was accepted by the committee members as a valid tool. The committee members indicated, for the study reach, Class II with tolerance of approximately 10%. The scenarios simulation using the QUAL-2E model indicated values of emission pattern for BOD, for the Class II in the wet and dry periods, of 6 mg/L. In the case the river is classified in the Class III, the values would be 20 and 17 mg/L for the wet and dry period, respectively. Although Class II is desired for the river classification by the committee, it was observed that the emission patterns would be too low for BOD, making its adoption impracticable, since the polluting activities are not capable of reaching such efficiency on their current stage. For the faecal coliforms, the emission pattern would be 103 MPN/100mL (dry period) and 104 MPN/100mL (wet period) in the case the river is classified in the Class II, whereas for the Class III, the emission pattern would be of the order of 105 MPN/100mL, for both wet and dry periods. According to the analysis performed in this thesis, the most adequate water quality classification for the Salgado River on the reach between the Batateira Fountain and the Missão Velha Waterfall, on the current conditions, is the Class III with tolerance of 10%